고구마 무병묘의 경삽 대량번식을 위한 플러그 규격과 적심 후 휘묻이 평가 - 이나라(Na-Ra Lee); 이승엽(Seung-Yeob Lee) (Weon'ye gwahag gi'sulji, 2019)
고구마 무병묘의 경삽을 이용한 플러그묘 생산과 묘상에서 경삽묘의 대량증식을 위하여, 4 품종(‘맛나미’, ‘신천미’, ‘연황미’, ‘신자미’)을 이용하여 플러그 셀 크기의 영향과 경정절단 파상휘묻이를 하여 생육특성을 조사하였다. 5cm 크기의 경삽묘를 버미큘라이트와 펄라이트 혼합배지(1:1, v/v)를 채운 50, 72, 105, 128구 플러그 트레이(54 × 28 × 5cm)에 삽목하여 NFT 수경베드에서 일본원시액을 공급하여 3주간 육묘하였다. 경정절단 파상휘묻이는 묘상에 10 × 30cm로 이식 후 3주째에 5cm 크기로 경정을 절단하여 휘묻이하였으며, 대조구는 10 × 10cm로 이식 후 경정절단없이 육묘하였다. 경삽묘의 줄기신장은 2주까지는 플러그 셀 크기에 따른 차이가 크지 않았으나, 3주후의 생장은 72구에서 가장 양호하였다. 엽수, 뿌리수 및 뿌리길이 등은플러그 셀 크기가 작아짐에 따라 감소하였다. 생체중 및 건물중은 상토량과 광조건이 유리한 50구와 72구 플러그에서 양호하였으며, 128구 플러그에서 유의한 감소를 보였다. 경정절단 파상휘묻이 처리는 이식 6주 후에 총 엽수, 곁순수, 평균곁순길이,생체중 및 건물중 등이 대조구보다 유의하게 증가하였다. 5cm 이상의 곁순수와 평균길이는 경정절단 파상휘묻이 처리에서 대조구보다 1.9배와 1.7배의 유의한 증가를 보였다. 따라서 고구마 무병묘 경삽을 위한 적정 플러그 크기는 육묘기간이 2주 내외일 경우는 105구, 3주 이상일 경우에는 72구에서 적합하였다. 농가에서 경삽묘의 묘상 대량증식은 경정절단 파상휘묻이법으로 육묘하는 것이 증식효율이 1.7배 높았다. To establish an efficient mass propagation method using stem cuttings of virus-free sweet potato[Ipomoea batatas (L.) Lam.] plantlets, the growth characteristics of four cultivars (‘Matnami’,‘Shincheonmi’, ‘Yeonhwangmi’, and ‘Shinzami’) influenced by plug cell size and pinching outfollowed by layering were investigated. Shoot tip cuttings of 5-cm length were grown in plug trayswith 50, 72, 105, and 128 cells filled with vermiculite and perlite (1:1, v/v) using the nutrient filmtechnique and the nutrient solution developed by the National Horticultural Experiment Station inJapan for 3 weeks. Shoot tip pinching out (5-cm length) followed by serpentine layerage (SPFSL)was performed after growth for 3 weeks with 10 × 30-cm spacing in nursery soil. The control plantletswere grown with 10 × 10-cm spacing without shoot-tip pinching and layering. Stem growth of plugplantlets was not different among the plug cell sizes up to 2 weeks, but growth after 3 weeks showedthe best elongation in 72 cells followed by 50-, 105-, and 128-cell plug trays. Number of leaves,number of roots, and the longest root length were reduced in proportion to cell volume. Freshweight and dry weight were high in 50- and 72-cell plug trays with more light and soil volume,while they were significantly reduced in 128-cell plug trays. At 6 weeks after transplanting, numberof leaves, number of side shoots, fresh weight, and dry weight were significantly increased inSPFSL plants compared to the control. Mean length and number of side shoots (over 5 cm) per plantin SPFSL plants were 1.9 and 1.7 times higher than the control. In this work, the plug cell size forstem cutting was economically suitable in 105-cell plug trays for 2 weeks, and in 72-cell plug traysover 3 weeks. The propagation of stem cutting by SPFSL for farmers was 1.7 times higher than thecontrol. KCI Citation Count: 4